2018
DOI: 10.1038/s41467-018-06192-3
|View full text |Cite
|
Sign up to set email alerts
|

Structures of insect Imp-L2 suggest an alternative strategy for regulating the bioavailability of insulin-like hormones

Abstract: The insulin/insulin-like growth factor signalling axis is an evolutionary ancient and highly conserved hormonal system involved in the regulation of metabolism, growth and lifespan in animals. Human insulin is stored in the pancreas, while insulin-like growth factor-1 (IGF-1) is maintained in blood in complexes with IGF-binding proteins (IGFBP1–6). Insect insulin-like polypeptide binding proteins (IBPs) have been considered as IGFBP-like structural and functional homologues. Here, we report structures of the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 70 publications
0
31
0
Order By: Relevance
“…This result differs from Susan Westfall’s findings, which showed that probiotics and synbiotics could downregulate dilp2 , enhance lean body mass, and extend longevity [ 4 ]. Several studies have also shown that increased expression of Imp-L2 could lead to phenotypic modulation, including increased stored lipids, decreased reproductive capacity, and extended lifespan [ 56 , 57 ]. These changes are in accordance with the downregulation of IIS.…”
Section: Discussionmentioning
confidence: 99%
“…This result differs from Susan Westfall’s findings, which showed that probiotics and synbiotics could downregulate dilp2 , enhance lean body mass, and extend longevity [ 4 ]. Several studies have also shown that increased expression of Imp-L2 could lead to phenotypic modulation, including increased stored lipids, decreased reproductive capacity, and extended lifespan [ 56 , 57 ]. These changes are in accordance with the downregulation of IIS.…”
Section: Discussionmentioning
confidence: 99%
“…Although proteins related to the IGFBP-rPs were also identified in Crustacea and reported to bind an ILP responsible for sexual differentiation (6), proteins corresponding to the “true” vertebrate IGFBP 1–6 were not identified in invertebrates. Instead, it seems that the function of IGFBPs is fulfilled by IBPs which are composed of two immunoglobulin-like (Ig) domains and bind ILPs (including human insulin and IGF-1) with nanomolar affinities (7). Recently, we solved the apo and holo crystal structures of 242 amino acid Drosophila imaginal morphogenesis protein-late 2 protein (Imp-L2) which is one of the insect IBPs (7).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it seems that the function of IGFBPs is fulfilled by IBPs which are composed of two immunoglobulin-like (Ig) domains and bind ILPs (including human insulin and IGF-1) with nanomolar affinities (7). Recently, we solved the apo and holo crystal structures of 242 amino acid Drosophila imaginal morphogenesis protein-late 2 protein (Imp-L2) which is one of the insect IBPs (7). We have shown that the ligand ( Drosophila ILP5 and human IGF-1) binding mode of Imp-L2 differs from that of IGFBPs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations